Regulating abortion after ectogestation - Räsänen, Joona (Journal of medical ethics, 2023)
A few decades from now, it might become possible to gestate fetuses in artificial wombs. Ectogestation as this is called, raises major legal and ethical issues, especially for abortion rights. In countries allowing abortion, regulation often revolves around the viability threshold—the point in fetal development after which the fetus can survive outside the womb. How should viability be understood—and abortion thus regulated—after ectogestation? Should we ban, allow or require the use of artificial wombs as an alternative to standard abortions? Drawing on Cohen, I evaluate three possible positions for the post-ectogestative abortion laws: restrictive, conservative and liberal. While the restrictive position appears untenable, I argue that the liberal and conservative positions can be combined to form a legally and morally coherent basis for post-ectogestative abortion legislation, offering an improvement from the point of both prolife and prochoice positions.